Incidences of pneumonitis associated with the combination of radiotherapy and immune checkpoint inhibitors in lung cancer: a systematic review and meta-analysis - Li, Jing; Zheng, Lingli; Liu, Chaomin; Liu, Wei; Li, Yan; Wang, Dan; Jiang, Ting (Frontiers in Oncology, 2025)
ObjectiveRecently, the therapeutic effects of the combination of radiotherapy (RT) and immune checkpoint inhibitors (ICIs) on lung cancer (LC) have piqued the interest of the scientific community. Clinical trials have confirmed that RT and ICI therapy exert synergistic therapeutic effects. However, treatment with the RT-ICI combination can lead to the occurrence of pneumonitis, limiting the implementation of the treatment plan, decreasing the tumor control rate, and inducing immunosuppressive pneumonitis and radiation pneumonitis. Therefore, this study performed a systematic review and meta-analysis of pneumonitis prevalence among patients with LC who were treated with a combination of ICIs and chemoradiotherapy (CRT).MethodsLiterature published between January 1, 2010, and October 15, 2023, were searched in the PubMed, Cochrane Library, Embase, and Web of Science databases by two authors. The primary outcomes analyzed in this study were the incidence rates of all-grade pneumonitis and ≥ grade 3 pneumonitis.ResultsThis study analyzed 53 studies involving 4226 patients. The pooled incidence rates of all-grade and ≥ grade 3 pneumonitis were 36.0% (95% confidence interval (CI): 30.0–41.0) and 3.0% (95% CI: 2.0–4.0), respectively. The all-grade pneumonitis incidence rates in Asian patients (51%; 95% CI: 38%–63%) were higher than those in non-Asian patients (26%; 95% CI: 22%–31%). Conventional RT was associated with higher rates of all-grade pneumonitis than stereotactic body radiation therapy (SBRT) (37%; 95% CI: 31%–42% vs. 26.0%; 95% CI: 20%–33%). Additionally, sequential immunotherapy was associated with higher rates of all-grade pneumonitis than concurrent immunotherapy ((38%; 95% CI: 31%–45% vs. 25.0%; 95% CI: 20%–30%)). Furthermore, anti-PD1 therapy was associated with higher rates of all-grade pneumonitis than PD-L1 therapy (40%; 95% CI: 32%–47% vs. 20.0%; 95% CI: 16%–24%). Similar incidence rates of ≥ grade 3 pneumonitis were reported in all included studies.ConclusionThis study suggests that the combination of ICIs and RT/CRT is a safe and feasible therapeutic regimen for patients with LC. However, these findings are based on observational studies and are associated with significant heterogeneity. Hence, large prospective studies are needed to validate the findings of this meta-analysis.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/#myprospero, identifier CRD42023485613.